Burnup calculation of the OECD VVER-1000 LEU benchmark assembly using MCNP6 and SRAC2006 - Nguyen, Huu Tiep; Nguyen Thi, Dung; Tran Viet, Phu; Tran Vinh, Thanh; Pham Nhu Viet, Ha (Nuclear Science and Technology, 2018)
The present work aims to perform burnup calculation of the OECD VVER-1000 LEU (low enriched uranium) computational benchmark assembly using the Monte Carlo code MCNP6 and the deterministic code SRAC2006. The new depletion capability of MCNP6 was applied in the burnup calculation of the VVER-1000 LEU benchmark assembly. The OTF (on-the-fly) methodology of MCNP6, which involves high precision fitting of Doppler broadened cross sections over a wide temperature range, was utilized to handle temperature variation for heavy isotopes. The collision probability method based PIJ module of SRAC2006 was also used in this burnup calculation. The reactivity of the fuel assembly, the isotopic concentrations and the shielding effect due to the presence of the gadolinium isotopes were determined with burnup using MCNP6 and SRAC2006 in comparison with the available published benchmark data. This study is therefore expected to reveal the capabilities of MCNP6 and SRAC2006 in burnup calculation of VVER-1000 fuel assemblies.